Ultra-Low Oxygen and Preconditioning Storage Regulate Ethylene Synthesis to Prevent Corky Disorders in ‘Fuji’ Apple - Riaño, Camila; Ribba, Tomás; Marchant, Juan I.; O’Brien, José A.; Contreras, Carolina; Zoffoli, Juan P. (Frontiers in Plant Science, 2022)
Corky disorders in apples represent a major problem for long term storage where controlled atmosphere (CA) is mainly used. Ultra-low oxygen (ULO) is an alternative to CA, which consists of low partial pressure of O2 to maintain a low metabolism in the apple fruit, achieving an effective decrease of the ethylene production and physiological disorders. The aim of this research was to study the effectiveness of short hypoxia period on development of cork physiological disorders during storage of apple. ‘Fuji’ apples were prestored under ULO (0.5 kPa O2) for two periods of time (15 and 30 days) and two temperatures (0 °C or 5 °C). Corky physiological disorders increased at 5 °C prestorage temperature; however, ULO treatments for 15 or 30 days at 0 or 5 °C achieved a significant reduction of corky disorders near to 1%, compared with control treatments. Additionally, a significant reduction on ethylene production up to 30 days was observed in ULO-treated fruit at 0 °C and 5 °C. ULO for 30 days at 0 °C and 5 °C increased the internal production of ethanol and acetaldehyde, causing a lower sensory quality, due to the presence of fermentative flavors in fruit stored at 5 °C. ULO of 15 days of conditioning decreased the relative expression of ethylene biosynthesis genes MdACS1 and MdACO1, resulting in a lower ethylene production.